Peran Interpol dalam Penyelesaian Kasus Kejahatan Siber Berdasarkan Konvensi Budapest On Cybercrimes - Siti Aura Fadhillah; Michelle Sharon Anastasia Matakupan; Britney Wilhelmina Berlian Mingga (Journal on Education, 2023)
Technological development, apart from having a positive impact, also has a negative impact. One of the crimes caused by the development and progress of information technology is a crime related to internet applications, which is often referred to as cybercrime. This category of crimes includes all types of crimes as well as their modus operandi, which are carried out by utilizing internet facilities and as a negative effect of using internet applications. The characteristics of cybercrime crimes that do not recognize national territorial boundaries make these crimes inseparable from the role of the Secretariat of the National Central Bureau (NCB)—Interpol Indonesia. NCB-Interpol Indonesia has an important role in conveying information about cyber crimes committed by foreign or Indonesian citizens, obtained from NCBs of other countries, to the competent authorities. The goals and tasks of ICPO-Interpol will be achieved when NCB-Interpol Indonesia participates in fighting cybercrime because they fulfill international obligations regulated by laws and international conventions that apply in Indonesia. Obstacles that arise in tackling cybercrime crimes are related to national borders and jurisdictions, differences in national law making it difficult to determine which law to apply, extradition treaties, and the process of identifying cybercrime perpetrators